Intertextuality of Organization and Career in Constructing the “Reality” of Change. - Hansen, Katharine (TAMARA: Journal of Critical Postmodern Organization Science, 2006)
This study envisions that both organizations and careers can be perceived as texts and examines the intertextuality of organizations and careers as organizations and individuals construct and reconstruct change through narrative. The study, exploratory in nature, investigates individual/career texts in the context of change and proposes an intertextual lens through which to juxtapose these texts with organizational texts. Reprinted by permission of the publisher.